The Implemantation of Community Policing Based of Independence Village to Realizing Security and Order in Country - et al., Sumarji (International Journal of Advanced Science and Technology, 2019)
This article aims to find out what is the basis of consideration of Bhabinkamtibmas building the government’s self-reliance-based community and the barriers experienced by Bhabinkamtibmas in building community government To realize security and order in the area of Tangkil Village Sragen District Sragen. The method of research is non-doctrinal, that is with the technique of data collection with the method of field research through interviews and research literature studies, then of all the data collected is conducted qualitative analysis. The results of the research showed that the role of Bhabinkamtibmas to build community development is through working professionally through the implementation of community development, early detection and mediation/negotiation aimed at Conducive condition in its region. As for some obstacles experienced by Bhabinkamtibmas is Bhabinkamtibmas member as the main stakeholder of Polmas still working, the limitation of ability especially in terms of provision of construction materials and the technique of communicating with Community, Bhabinkamtibmas assignment of more than one target village, there is no ongoing socialization of other police functions (Intel, Reserse, Traffic, Sabhara), the absence of the Office of the Police and Community Partnership Hall (BKPM).